2021
DOI: 10.3390/microorganisms9071356
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium matutinum Causing Avian Malaria in Lovebirds (Agapornis roseicollis) Hosted in an Italian Zoo

Abstract: Avian malaria is a worldwide distributed, vector-born disease of birds caused by parasites of the order Haemosporida. There is a lack of knowledge about the presence and pathogenetic role of Haemosporida in Psittacidae. Here we report a case of avian malaria infection in lovebirds (Agapornis roseicollis), with the genetic characterization of the Plasmodium species involved. The birds were hosted in a zoo located in Italy, where avian malaria cases in African penguins (Spheniscus demersus) were already reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Several pieces of literature denoted the parasitic infection in pet birds and another investigation determines the coccidian intestinal parasites' high risk of infection in professional workers, for example, veterinarians' biologists, workers, tradesmen, and farm owners ( Krone and Cooper, 2002 ). A first point to note is that our study confirms the findings of other studies that show coccidiosis is one of the most frequently reported diseases of birds worldwide ( Cocumelli et al., 2021 ). This protozoan disease is responsible for significant worldwide economic losses to the poultry industry, with an estimated world annual loss of more than 3 billion USD ( Dkhil, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several pieces of literature denoted the parasitic infection in pet birds and another investigation determines the coccidian intestinal parasites' high risk of infection in professional workers, for example, veterinarians' biologists, workers, tradesmen, and farm owners ( Krone and Cooper, 2002 ). A first point to note is that our study confirms the findings of other studies that show coccidiosis is one of the most frequently reported diseases of birds worldwide ( Cocumelli et al., 2021 ). This protozoan disease is responsible for significant worldwide economic losses to the poultry industry, with an estimated world annual loss of more than 3 billion USD ( Dkhil, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…Birds are an integral part of virtually every ecosystem, and it is not surprising that they are commonly found in households and zoos worldwide ( Attia and Salem, 2022 ; Cocumelli et al, 2021 ). Many serious pathogens can infect avian spp., including bacteria ( Abd El Hamid et al, 2019 ; Marouf et al, 2020 , Marouf et al., 2022 ), viruses ( Setta et al, 2018 ), parasites, and fungi, as well as environmental and management stressors, revealing in severe economic losses ( Abd El-Hack et al, 2021a , b ; 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium matutinum (pLINN1) lineage is common in wild birds in Austria [ 4 , 13 ] and pathogenic for local endemic birds in New Zealand [ 12 , 52 ], where it was probably introduced together with their Turdus host species. The same lineage was recently reported to cause lethal malaria in captive African penguins Spheniscus demersus and Lovebirds Agapornis roseicolli in Italy [ 37 , 53 ], and Atlantic puffins Fratercula arctica in Switzerland [ 54 ]. These and other exotic to Europe bird species likely are non-adapted to pLINN1 infection.…”
Section: Discussionmentioning
confidence: 85%
“…[53]Espirito Santo, Brazil1 Puffinus puffinus rehabilitation centreCocumelli et al . [54]Central Italy2 Agapornis roseicollis zooMeister et al . [55]Berne Animal Park, Switzerland4 Fratercula arctica zooThorel et al .…”
Section: Resultsmentioning
confidence: 99%